Large-bowel obstruction caused by cancer: a prospective study. Issue 6189 (1st September 1979) - Fielding, L P; Stewart-Brown, S; Blesovsky, L
Abstract : Patients with obstructing large-bowel cancer may be treated by primary tumour resection or the conventional staged tumour resection, and a prospective study comparing these two treatments was carried out. The post-operative outcome in 174 patients (of whom 90 underwent primary and 47 staged tumour resection) showed that the overall mortality was similar in both groups but that the duration of hospital stay in patients who underwent primary tumour resection was half that of those who underwent staged tumour resection. The mortality for primary tumour resection, however, was unexpectedly high for lesions proximal to the splenic flexure and unexpectedly low for lesions distal to this point. Of patients with distal tumours in whom a staged resection was planned, 35% died after a loop colostomy. The most striking result was that the ratio of postoperative death for trainee surgeons compared with fully trained surgeons was 3:1. It is concluded that patients with large-bowel cancer who present with intestinal obstruction should be treated by a fully trained surgeon and that immediate resection of the tumour should be considered for every patient.